2001
DOI: 10.1021/ma0018796
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations of Hyperbranched Polymers in Shear Flows

Abstract: Brownian dynamics simulations of hyperbranched polymers with different degrees of branching have been performed under the influence of simple shear flow. Hydrodynamic and excludedvolume interactions have been taken into account explicitly. Shear-thinning effects have been observed for all simulated degrees of branching. As the molecular weight of highly branched structures increases, the zero shear rate intrinsic viscosity reaches a maximum and begins to fall similar to the intrinsic viscosity behavior of perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 24 publications
5
53
0
2
Order By: Relevance
“…The main group of HPs were irregular molecules resulting from the same sequential addition process used by Lyulin et al 14 Within this group, the HPs had the same degree of polymerization ͑N͒ as dendrimers of generations 4, 5, and 6 ͑i.e., Nϭ94, 190, 382͒. Lyulin et al revealed that simulated intrinsic viscosity values for these dendrimers peak near generation 5 (Nϭ190).…”
Section: ͑21͒mentioning
confidence: 99%
See 4 more Smart Citations
“…The main group of HPs were irregular molecules resulting from the same sequential addition process used by Lyulin et al 14 Within this group, the HPs had the same degree of polymerization ͑N͒ as dendrimers of generations 4, 5, and 6 ͑i.e., Nϭ94, 190, 382͒. Lyulin et al revealed that simulated intrinsic viscosity values for these dendrimers peak near generation 5 (Nϭ190).…”
Section: ͑21͒mentioning
confidence: 99%
“…Lyulin et al revealed that simulated intrinsic viscosity values for these dendrimers peak near generation 5 (Nϭ190). 14,39 At each N, HP molecules with DB ϭ0.4, 0.6, and 0.8 were specified. For each of these DBs, at each N, two to three molecules were created having distinct Wiener indices selected according to a systematic procedure ͑detailed below͒.…”
Section: ͑21͒mentioning
confidence: 99%
See 3 more Smart Citations